Child marriage and psychological well-being in Niger and Ethiopia - Neetu A. John; Jeffrey Edmeades; Lydia Murithi (BMC, 2019)
Abstract Background Despite an understanding of the circumstances of child marriage, including how it limits agency and erodes childhood support systems, not much is known about the relationship between child marriage and mental health of child brides, especially in the sub-Saharan African context. To address this gap, we use large-scale population-based data from ever-married women aged 18-45 in Niger (n = 2764) and Ethiopia (n = 4149) to examine the association of child marriage with overall psychological well-being and its sub-domains: depression, anxiety, positive well-being, vitality, self-control and general health. We complement this with qualitative data from Ethiopia to further contextualize the psychological well-being of child brides. Methods Multivariate linear regressions were conducted to estimate the association between child marriage and overall psychological well-being and its sub-domains. Thematic qualitative analysis was conducted to further understand the lives of child brides. Results Our regression analysis found significant negative associations between very early marriage (marriage at 15 years or earlier) and overall psychological well-being in both Niger and Ethiopia. With the exception of self-control, all sub-domains of psychological well-being - depression, anxiety, positive well-being, vitality and general health - were negatively associated with very early marriage. In addition, in the qualitative analysis, Ethiopian child brides reported suffering emotional distress and depression induced by the burden of handling marital responsibilities at an early age. Conclusion The study highlights that even in settings where child marriage is normative, marrying very early is associated with negative outcomes. Further research is needed to understand the mechanisms that make those married during early adolescence particularly vulnerable to psychological distress, so that programs can address those vulnerabilities.